Restoration of terre de barre fertility using pigeonpea grown in rotation or intercropping with maize in the derived savanna of Benin - Aihou, K.; Sanginga, Nteranya; Vanlauwe, Bernard; Diels, J.; Merkx, R; Cleemput, O. van (2008)
The following nine main cropping systems were evaluated: maize/maize in rotation without N-fertilizer (control); maize/cowpea in rotation where maize received N-fertilizer; maize/pigeonpea intercropping without N-fertilizer; maize/cowpea/pigeonpea in rotation where maize received N-fertilizer; maize/maize in rotation with N-fertilizer; maize/pigeonpea fallow in rotation where maize received N-fertilizer; maize/pigeonpea intercropping where maize received N-fertilizer; pigeonpea/maize/cowpea in rotation where maize received N-fertilizer; pigeonpea/maize/maize where maize received N-fertilizer. The rate of N-fertilizer applied was 74 kg N as urea (28 kg N/ha 2 weeks after planting maize and 46 kg N/ha 6 weeks after planting maize). Compared to the control, the increase in maize grain yield ranged from 1.55 to 215 % for all cropping systems receiving N-fertilizer and intercropping without N-fertilizer, maize grain yield in intercropping without N-fertilizer increased by 9 % in first year and decreased by 1.55 % in second year compared to the control. The maize stover yield with N-fertilizer application increased by -24 up to 203 %. Pigeonpea grain yield (in intercropping) without N-fertilizer was 56 % higher than with N-fertilizer. Pigeonpea as fallow produced 73-97 % more fresh wood than intercropped pigeonpea without fertilization and 91-118 % more fresh wood than intercropped pigeonpea with N-fertilizer. The intercropped Cajanus cajan with N-fertilizer produced 11 % less fresh wood than intercropped without N-fertilizer. The total N amount in the maize grain yield increased by 5-245 % for the first season of year 1 compared to the control and increased by 241-260 % for the second season of year 1 compared to the control. The total N amount in the maize grain of the intercropped pigeonpea/maize with N-fertilizer was 190 % higher than the intercropped pigeonpea/maize without N-fertilizer. The total amount of P follows the same trend as N- fertilizer in intercropped systems. The yield efficiency was low in year 1 compared to year 2. The Land Equivalent Ratio (LER) was higher in cropping system without N-fertilizer than with N-fertilizer.